DEVELOPMENT OF A HIGH-PERFORMANCE HOLDING MACHINE WITH COMPLEX SPATIAL MOVEMENT OF TWO WORKING CAPACITIES - ZALYUBOVSKYI, Mark; PANASYUK, Igor (Herald of Khmelnytskyi National University. Technical sciences, 2022)
A new design of the galvanizing machine is proposed, which is equipped with two working tanks that perform complex spatial movement. The structure and principle of operation of the developed design of the machine are accurately described. The developed design of the machine with two capacities that perform complex spatial movement allows to increase considerably productivity of processing of details due to the fact that there is a possibility to carry out two different thawing technological operations on one machine or to process two parties of different details at the same time. The design of the machine, during operation, allows to involve in working process, both both working capacities, and one. Equipping the machine with a special drive design with four Hook hinges allows to reproduce the required law of change of angular velocity on each driving shaft of the machine, the implementation of which will create conditions that will ensure the same intensity of the working array between opposite ends of the tank in opposite directions. process, as well as uniform dynamic loading of all moving parts. Analytical studies were performed, within which some geometrical parameters of the machine design were determined, in particular, the value of the angle α between the axes of the shafts of each Hook hinge was established, which will ensure the implementation of the required angular velocity law on the machine drive shaft. The relationship between the extreme values of the law of change of the angular velocity of the driving shafts of the machine and the magnitude of the angles in each Hook hinge is established. The obtained results of analytical research can be used in the relevant design offices of machine-building enterprises at the stage of designing galvanizing equipment with complex spatial movement of working tanks.